TypeScript quickly - Fain, Yakov; Moiseev, Anton (Manning Publications, 2020)
I've seen the future and it is TypeScript--Yakov Fain and Anton Moiseev will take you there. Guy Langston, Axio Quant TypeScript is JavaScript with an important upgrade! By adding a strong type system to JavaScript, TypeScript can help you eliminate entire categories of runtime errors. In TypeScript Quickly , you'll learn to build rock-solid apps through practical examples and hands-on projects under the expert instruction of experienced web developers Yakov Fain and Anton Moiseev. about the technology Strong typing can eliminate nearly all errors caused by unanticipated data values. With TypeScript, an enhanced version of JavaScript, you can specify types and type annotations so your code is easier to read and far less likely to fail at runtime. And because the core of TypeScript is standard JavaScript, it runs on all major browsers and can be used with frameworks like Angular, Vue, and React. about the book TypeScript Quickly teaches you to exploit the benefits of types in browser-based and standalone applications. In this practical guide, you'll build a fascinating blockchain service app that takes you through a range of type-sensitive programming techniques. As you go, you'll also pick up valuable techniques for object-oriented programming with classes, interfaces, and advanced features such as decorators and conditional types. what's inside Mastering TypeScript syntax Using TypeScript with JavaScript libraries Tooling with Babel and Webpack Developing TypeScript apps using Angular, React, and Vue about the audience For web developers comfortable with JavaScript and HTML. about the authors Yakov Fain and Anton Moiseev are experienced web developers. They have authored two editions of Manning's Angular Development with TypeScript. TypeScript is the most important language to learn today, and this book is a perfect way to learn it. Jerry Stralko, Wolters Kluwer Great resource to get started with and to master TypeScript. Deniz Vehbi, Tesco A well-paced book that benefits greatly from the experience of the authors. George Thomas, Manhattan Associates.